Introducing the Implicit Dynamics of Generation Z's Consumer Behaviour: An Exploratory Factor Analysis - Tiwari, Anju; Sinha, Dr Rohit (Southeast Asian Business Review, 2026)
This study applies exploratory factor analysis (EFA) to explore the latent variables impacting Z- Generation customer buying habits. With the help of surveys, useful information about various facets of customer choices and preferences is gathered. Five main latent factors are identified with the help of analysis: Psychological concern, Physiological Concern, Sociological concern, Ethical Concern and Personal concern. To gather the information about the required data around 150 questionnaires are distributed out of which more than 100 samples are auxiliary utilized for data analysis. Family values and cultural acceptance, environmental concerns, gender impact, amusement motive, community involvement etc. are measured as key components with the help of the survey and then all of them are grouped accordingly under five common heads as stated above so as to research consumer behavior broadly. To successfully interact with Z-Generation customers, useful information is provided for companies. More focused marketing strategies may be created in lining up with the preferences and believes of Z-Generation by realizing these latent characteristics, which will ultimately result for increase in loyalty and brand engagement. The study's findings might be examined more thoroughly and explored for cross-cultural differences as well as longitudinal trends and to measure the extent to what new technology may impact the purchasing behaviour of Z- Generation.